Study of Erythrocyte Indices, Erythrocyte Morphometric Indicators, and Oxygen-Binding Properties of Hemoglobin Hematoporphyrin Patients with Cardiovascular Diseases - Victor V. Revin; Antonina A. Ushakova; Natalia V. Gromova; Larisa A. Balykova; Elvira S. Revina; Vera V. Stolyarova; Tatiana A. Stolbova; Ilya N. Solomadin; Alexander Yu. Tychkov; Nadezhda V. Revina; Oksana G. Imarova (Advances in Hematology)
The current study investigates the functional state of erythrocytes and indices of the oxygen-binding capacity of hemoglobin in blood samples from healthy donors and from patients with coronary artery disease and myocardial infarction before and after treatment. It has been established that, in cardiovascular diseases, erythrocyte morphology and hemoglobin oxygen-transporting disorders are observed. Standard therapy does not result in the restoration of the structure and properties of erythrocytes. The authors believe that it is necessary for future therapeutic treatment to include preparations other than cardiovascular agents to enhance the capacity of hemoglobin to transport oxygen to the tissues.